2(12-w)=-2(w-17)

Simple and best practice solution for 2(12-w)=-2(w-17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(12-w)=-2(w-17) equation:



2(12-w)=-2(w-17)
We move all terms to the left:
2(12-w)-(-2(w-17))=0
We add all the numbers together, and all the variables
2(-1w+12)-(-2(w-17))=0
We multiply parentheses
-2w-(-2(w-17))+24=0
We calculate terms in parentheses: -(-2(w-17)), so:
-2(w-17)
We multiply parentheses
-2w+34
Back to the equation:
-(-2w+34)
We get rid of parentheses
-2w+2w-34+24=0
We add all the numbers together, and all the variables
-10!=0
There is no solution for this equation

See similar equations:

| x-1/11=10/11 | | W+7w=24 | | z=7z+2-2z | | v-2/3=81/2 | | 6(2p-5=18 | | 3/4x-+14=3 | | 5×(18-4y)+y=33 | | -5(4y-2)+9y=4(y+7) | | -8(u-2)=0 | | Y+9y=54 | | -10(x-7)=-30 | | –10(x-7)=-30 | | -6(t-1)=0 | | –10(x-7)=–30 | | 6+2(2u-2)=-2(6u-4)+u | | 2x-31=-11 | | X-2y-14=0 | | -0.85(c+3)=3.4 | | 9(w+2)=-8w-33 | | 71=7x-6 | | 0.25n-0.75=0.50 | | -9.39-3.4x=-1.1x+11.08 | | 2x+5+4x=6x+3 | | 5x+5+4x=6x+3 | | 3f-15=42 | | 2x+5-4x=6x+3 | | -4*10+y=9 | | 2x+9x-39=0 | | 7-5+3x-1=3+7 | | 7j-5=6j | | -16x+4=20-2x | | 7-7b=-6b |

Equations solver categories